Caregivers: behavior and practices in dysphagia - de Mendonça, Marlos Suenney; Português, Português (Revista de Investigación en Logopedia, 2025)
Swallowing is essential for human survival. However, dysphagia, characterized by difficulty in swallowing food and liquids, can negatively impact quality of life. This study aims to identify the behaviors, practices, and challenges faced by caregivers in managing dysphagia from a speech therapy perspective. We conducted the research in two municipalities in Sergipe, Brazil, interviewing seven caregivers of patients diagnosed with dysphagia. Using a qualitative approach and Bardin’s content analysis technique to analyze the data, we found that caregivers face significant challenges, including emotional burden, changes in routine, and difficulties in food management. Despite recognizing the importance of speech therapy, some caregivers encountered difficulties in implementing recommended strategies at home. The results underscore the need for support for caregivers of individuals with dysphagia, including proper guidance and access to support resources. Training strategies and interventions to promote mental health are essential to enhance the quality of life of these caregivers.